Hubungan Pengetahuan Dan Status Ekonomi Terhadap Kejadian Stunting Di Kelurahan Tonrokassi Timur Di Wilayah Kerja Puskesmas Tamalatea Kabupaten Jeneponto - Andi Tenri Angka; Yenni Yenni (Pusat riset dan Inovasi Nasional, 2022)
Stunting is defined as the condition of children aged 0 – 59 months, where the height for age is below minus 2 standard deviations (<-2SD) from the WHO median standard. It is further said that stunting will have an impact and is associated with disrupted brain development processes, which in the short term will affect cognitive abilities. The aim of the research is to determine the relationship between knowledge and economic status on the incidence of stunting in the East Tonrokassi Village in the working area of ​​the Tamalatea Community Health Center, Jeneponto Regency. The type of research used is Cross Sectional Study. The sample in this study was all toddlers who experienced stunting in the East Tonrokassi Village in the working area of ​​the Tamalatea Community Health Center, Jeneponto Regency, totaling 31 toddlers using the total sampling technique. The results of the research state that there is a relationship between knowledge and the incidence of stunting (p value = 0.000 < 0.05), there is a relationship between economic status and the incidence of stunting (p value = 0.000 < 0.05). The conclusion is that there is a relationship between knowledge and economic status and the incidence stunting in East Tonrokassi Village in the working area of ​​the Tamalatea Community Health Center, Jeneponto Regency. It is hoped that nutrition officers and cadres can increase posyandu visits and carry out health promotions about stunting to the community